Effects of different levels of oxalic acid administration on feed intake and nutrient digestibility in goats - Mohammad Mijanur Rahman,; Md. Rokibur Rahman,; Niimi, Mitsuhiro; Wan Embong Wan Khadijah,; Akashi, Ryo; Ramli Abdullah, (Penerbit Universiti Kebangsaan Malaysia, 2017)
An experiment was carried out to investigate the effects of oxalic acid administration on feed intake and nutrient digestibility in goats. Four female cross bred (Boer × local) goats (average body weight of 46.3 kg) were randomly assigned to four experimental diets including oxalic acid administration at levels of 0, 2.25, 4.50 and 6.75 g/animal/d in a 4×4 Latin Square design. Oxalic acid diluted with water was administered orally via syringe to experimental goats once daily for four experimental periods. Each experimental period was lasted 21 d in length, comprising 14 d of adaptation to the experimental diet followed by 7 d of data collection. All the animals were individually fed with Napier grass ad libitum supplemented with 300 g (fresh basis) pelleted compound feed per goat per day throughout the study. Feed composition, feed intake, nutrient intake and nutrient digestibility were determined. Intakes of dry matter (DM), organic matter (OM), crude protein (CP), neutral detergent fibre (NDF) and metabolisable energy tended to linearly decrease with the increasing rate of oxalic acid administration, with the value in the 6.75 g oxalic acid/animal/d treatment being significantly (p<0.05) lower than the control (0 g oxalic acid/animal/d) treatment. The oxalic acid administration had no effect on apparent digestibilities of DM, OM, CP and NDF. The experiment demonstrated that oxalic acid administration may influence in the DM and nutrient intakes, but not influence on DM and nutrient digestibilities in goats.